Perancangan Sistem Informasi Website Terminal Giri Adipura Wonogiri Dengan Menggunakan Wordpress - Rivai, Bachtiar, Nurgiyatna, S.T., M.Sc., Ph.D (2017)
Terminal Giri clean city built since 1988 were first named Terminal Krisak. Along with the changing times and the number of passengers is increasing the Terminal Giri clean city formerly known as Terminal Krisak in renovation wider than ever. The absence of media to deliver information online about the clean city Giri Terminal, Terminal Giri Therefore Verse necessitates communication media. The subject matter contained herein author makes the design of information systems Giri Verse Terminal Wonogiri website using wordpress, which aims to be the community or user of website visitors and passengers can obtain information easily about Giri Terminal Wonogiri clean city. Permbuatan website Giri Verse Terminal contains information about news, facilities, and contacts from a bus agent that is in Terminal Wonogiri Giri clean city. Testing of information systems Terminal Giri website is done to clean city transportation department employee who served in Terminal Giri clean city and community Wonogiri age or visitor friendly website. The author interviewed the service officer perhubugan Giri Verse Terminal Wonogiri, according to their website is very helpful in disseminating information. In addition to interviews with the transportation department Giri Verse Terminal Wonogiri here the authors also conducted interviews with the general public or a visitor friendly website, according to their website is very helpful in getting information and book bus tickets in Terminal Wonogiri Giri clean city.